Model for human skin reconstructed in vitro composed of associated dermis and epidermis - Souto, Luís Ricardo Martinhão; Rehder, Jussara; Vassallo, José; Cintra, Maria Letícia; Kraemer, Maria Helena Stangler; Puzzi, Maria Beatriz (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: The technique of obtaining human skin with dermis and epidermis reconstructed from cells isolated from patients can enable autologous skin grafting on patients with few donor sites. It also enables in vitro trials on chemicals and drugs. The objective of this work was to demonstrate a method for obtaining hu- man skin composed of associated dermis and epidermis, reconstructed in vitro. DESIGN AND SETTING: Experimental laboratory study, in the Skin Cell Culture Laboratory of Faculdade de Ciências Médicas, Universidade Estadual de Campinas. METHODS: Cells from human fibroblast cultures are injected into bovine collagen type I matrix and kept immersed in specific culturing medium for fibroblasts. This enables human dermis re- construction in vitro. On this, by culturing human keratinocytes and melanocytes, differentiated epidermis is formed, leading to the creation of human skin composed of associated dermis and epidermis, reconstructed in vitro. RESULTS: We showed that human skin composed of associated dermis and epidermis can be suc- cessfully reconstructed in vitro. It is histologically formed in the same way as human skin in vivo. Collagen tissue can be identified in the dermis, with cells and extracellular matrix organized in parallel to multilayer epidermis. CONCLUSIONS: It is possible to obtain completely differentiated human skin composed of associ- ated dermis and epidermis, reconstructed in vitro, from injection of human fibroblasts into bovine collagen type I matrix and culturing of human keratinocytes and melanocytes on this matrix.